RANCANG BANGUN DAN MONITORING ALAT JEMUR PAKAIAN BERBASIS WEB MENGGUNAKAN METODE NAIVE BAYES - La Ode Ichsan Chumaidi; Isnawaty Isnawaty; Nur Fajriah Muchlis (Informatics Engineering Department of Halu Oleo University, 2018)
Today's weather changes are unpredictable, caused by global warming. The dry season and the rainy season are unpredictable. Because it is human activity to dry clothes quite disturbed by the arrival of heat and rain are uncertain.The solution of the problem is an automatic drying tool, a clothes drying tool that can move in and out direction and into the home miniature automatically based on weather conditions and ambient light. The working principle of this automatic drying tool is using a switch controlled by a microcontroller that receives input values from three sensors. The value of the calculation of Naive Bayes will be classified into two categories namely drag and drying. At the time of rain classification value > no rain then the clothesline will move automatically into miniature house.This tool is controlled by microcontroller with three sensors namely DHT11 sensor, LDR (Light Dependent Resistor) and water sensor and has a DC motor output. This tool uses NodeMCU L298N is used to drive a DC motor and connect to the Web.Keywords—Automatic Drying Tool, Naive Bayes, Microcontroller, NodeMCU l298N. DOI : 10.5281/zenodo.1402834